Estudo fitoquímico e biológico das folhas de Banisteriopsis argyrophylla (A. Juss.) B. Gates (Malpighiaceae) - Oliveira, Daiane Maria (2016)
With the increasing fungi resistance compared with existing drugs on the market and the side effects reported by some compounds with antioxidant properties and enzymatic inhibitors, in particular against α-amylase and α-glucosidase, the discovery of new compounds with biological potential, becomes a need. In this context, natural products can be an important source for the discovery of new active molecular architectures. Then, this study aimed to evaluate the antioxidant activity, the enzymatic inhibitory activity of α-amylase and α-glucosidase, the antifungal and cytotoxic activities of ethanolic extract (EE) the leaves of Banisteriopsis argyrophylla (Malpighiaceae) and their fractions, obtained by liquid-liquid extraction using solvents of increasing polarity. The antioxidant activity was evaluated by the free radical DPPH scavenging method (2,2-diphenyl-1-picrylhydrazyl) and the ethyl acetate fractions (FAE) and n-butanol (FB) were the most active, confirmed by the peak current and the oxidation potential obtained by differential pulse voltammetry (DPV). The inhibitory activity of the α-amylase and α-glucosidase was analyzed considering the reactions between substrates α-(2-chloro-4-nitrophenyl)-β-1,4-galactopiranosilmaltoside (Gal-α-G2-CNP) and 4-nitrophenyl-α-D-glucopyranoside (p-NPG), respectively. Initially, it was found that the EE showed considerable activity against α-amylase (EC50 = 2.89±0.1 μg m L–1) compared to the acarbose used as positive control (EC50 = 0.08±0.1 μg mL–1) and that did not showed promising activity against the α-glucosidase. After this observation we evaluated the inhibitory activity of α-amylase fractions, with FAE (EC50 = 2.33±0.1 μg mL–1) and FB (EC50 = 2.57 ± 0.1 μg mL–1) showing the best inhibitions. The antifungal activity was evaluated against Candida species, and the FAE had better antifungal potential (MIC's between 93.75 and 11.72 μg mL–1) compared with amphotericin as positive standard (MIC = 1.00 and 2.00 μg L–1 for C. parapsilosis and C. krusei used as controls, respectively). The EE (CC50 = 360.00 ± 12 μg mL–1) and fractions (CC50's> 270.00 μg mL–1) were considerably less toxic to Vero cells than the cisplatin used as positive control (CC50 = 7.01 ± 0 6 μg mL–1). The FAE showed the best results for the activities studied, this fraction was submitted to ultra performance liquid chromatography coupled with mass spectrometry (UPLC-MS)), and the following flavonoids have been identified: (±)-catechin, quercetin-3-O-β-D-Glc/ quercetin-3-O-β-D-Gal, quercetin-3-O-β-L-Ara, quercetin-3-O-β-D-Xyl, quercetin-3-O-α-L-Rha, kaempferol-3-O-α-L-Rha, quercetin-3-O-(2''-galoil)-α-L-Rha, quercetin-3-O-(3''-galoil)-α-L-Rha and kaempferol-3-O-(3''-galoil)-α-L-Rha,. FAE was submitted to column chromatography using C18 phase, and (±)-catechin was isolated (FAE-A1, 73 mg) and three fractions consisting of a mixture of flavonoids were obtained (FAE-A2, FAE-A3 and FAE-A4). These compounds were identified by thin layer chromatography (TLC) and (–)-ESI-MS. The (±)-catechin fraction showed an MIC = 2.83 μg ml–1 in assay using C. glabrata, with amphotericin as positive control. The fractions FAE-A2, FAE-A3, FAE-A4, showed less antifungal potential in tested concentrations. The identified flavonoids are described in the literature, regarding their antioxidant capacity and (±)-catechin, quercetin-3-O-Rha and kaempferol-3-O-Rha are described as α-amylase inhibitors. Thus, B. argyrophylla is an important species that produces compounds with antioxidant potential that can be related to the traditional use as anti-inflammatory and also has antifungal compounds and inhibitors of α-amylase. Therefore, these leaves are promising resources for the production of new drugs.